2011
DOI: 10.3341/kjo.2011.25.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Changes in a Rat Model of Oxygen-Induced Retinopathy

Abstract: PurposeTo identify altered patterns of retinal mRNA expression in a rat model of oxygen-induced retinopathy (OIR).MethodsSprague-Dawley rats from P2 to P14 were exposed to hyperoxia (80% oxygen) to induce OIR and then returned to normoxic conditions. Control rats were sustained in room air. Retinal gene expression between the rats of OIR and the controls was compared using cDNA microarray analysis. Reverse transcriptase polymerase chain reaction (RT-PCR) was used to verify the microarray results.ResultsAmong a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Accumulating evidence has demonstrated that NFATc4 exerts a proapoptotic effect in multiple diseases, and might participate in retinal ganglion cell apoptosis [ 100 ]. The proteoglycan decorin, encoded by the Dcn gene from the group, may also play a role in the differentiation of retinal ganglion cells [ 101 ] and is involved in hypoxic retinal damage, significantly reduce in expression in oxygen-induced retinopathy [ 102 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that NFATc4 exerts a proapoptotic effect in multiple diseases, and might participate in retinal ganglion cell apoptosis [ 100 ]. The proteoglycan decorin, encoded by the Dcn gene from the group, may also play a role in the differentiation of retinal ganglion cells [ 101 ] and is involved in hypoxic retinal damage, significantly reduce in expression in oxygen-induced retinopathy [ 102 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although several papers have employed gene chips to analyze expression in murine OIR models of ROP [144-147], only one (to our knowledge), Recchia et al [40], did so in the 50/10 ROP rat. Thus, in our study, genes were deemed ‘regulated’ if the fold change (FC) was greater than 1.7, up (+0.77 log 2 ) or down (-0.77 log 2 ), for easy comparison to Recchia et al 's gene chip results wherein this was the cutoff used for significance.…”
Section: Methodsmentioning
confidence: 99%
“…Decrease in decorin levels can reflect cellular damage and cell death whilst the recovery of decorin can occur in response to retinal regenerative processes or be associated with several inflammatory responses. Oxygen induced retinopathy (OIR) in Sprague–Dawley rats displayed significant decrease in decorin expression as compared to their controls [ 42 ]. Another study also found similar results whereby OIR rats with severe retinal injury and neuronal cell death presented significantly reduced decorin mRNA and protein expression [ 43 ].…”
Section: Class I Retinal Slrpsmentioning
confidence: 99%